Methylation of MTHFR Moderates the Effect of Smoking on Genomewide Methylation Among Middle Age African Americans - Andersen, Allan M.; Lei, Man-Kit; Philibert, Robert A.; Beach, Steven R. H. (Frontiers in Genetics, 2018)
Differential methylation at MTHFR (mMTHFR) has been examined previously as a moderator of changes in methylation among nascent smokers, but the effects of mMTHFR on genomewide patterns of methylation among established smokers in middle age are unknown. In the current investigation we examined a sample of 180 African American middle-aged smokers and non-smokers to test for patterns indicative of three different potential mechanisms of impact on epigenetic remodeling in response to long-term smoking. We found that mMTHFR moderated the association between smoking and changes in methylation for more than 25% of the 909 loci previously identified as being associated with smoking at a genomewide level of significance in middle-aged African Americans. Observed patterns of effect indicated amplification of both hyper and hypo methylating responses to smoking among those with lower mMTHFR. Moderating effects were robust to controls for sex, age, diet, and cell-type variation. Implications for potential mechanisms conferring effects are discussed. Of particular potential practical importance was a strong effect of mMTHFR on hypomethylation at GPR15 in response to smoking, indicative of the differential impact of MTHFR activity on changes in a specific cell population linked to inflammatory disease in smokers.